Pengaruh lama fermentasi dan penambahan asam asetat terhadap karakteristik nata de soya dari limbah tahu - Mukhammad Nasor; Hapsari Titi palupi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Liquid waste from tofu processing still contains nutritional components that can be utilized as nata de soya products using Acetobacter xylinum bacteria through simple fermentation. The processing of nata de soya is influenced by environmental conditions and the fermentation period. This study aimed to determine the effect of the fermentation period and the addition of acetic acid on the quality of nata de soya. The method used in this study was a randomized block design consisting of 2 factors, namely fermentation period (10 days; 13 days; 16 days) and acetic acid concentration (2%; 2.5%; 3%). The parameters observed included moisture content, ash content, protein content, pH, yield, thickness, and hardness. The results showed that the treatment of the fermentation period had a significant effect on moisture content, ash content, protein, pH, thickness, yield, and hardness, while the concentration of acetic acid had a significant effect on water content, ash content, pH, yield, and thickness. The treatment of fermentation period for 16 days and acetic acid concentration of 2% is the best treatment with characteristic values, namely moisture content of 88.93%, ash content of 94.77%, protein content of 2.99%, pH 3.97, yield of 18.88%, thickness of 19.90 mm, and hardness of 84.87 g/cm2.